INTEGRATION OF GENDER VERIFICATION MECHANISM TO AUTHENTIATE VOICE FOR GOOGLE CLOUD SPEECH TO TEXT - Sonal, Mahima Dahiya (International Journal of Advanced Science and Technology, 2020)
Voice recognition system along with its application has been introduced in this research. The building block of voice recognition process such as feature extraction, acoustic model, language model, word lexicon, pattern classification, confidence scoring has been explained